The Significance of Touch in Pediatric Physiotherapy - Sørvoll, Marit; Øberg, Gunn Kristin; Girolami, Gay L. (Frontiers in Rehabilitation Sciences, 2022)
Change in theoretical framework over the last decades and recent research in pediatric physiotherapy, has created a debate surrounding therapeutic touch. What is the role of or is there a need for handling and hands-on facilitated guidance (facilitation)? Does it limit and/or interfere with children’s learning and development? It is frequently argued that therapeutic touch represents a passive and/or static approach that restricts disabled children`s participation during interaction and activity in clinical encounters leading to decreased home, school and community participation. Touch may even appear as coercive and controlling. In this context, therapeutic touch is largely associated with physical hands-on activities. However, therapeutic touch can also be understood as an intersubjective phenomenon that arises from a deep connection between movement, perception, and action. We believe the significance of therapeutic touch and its impact on physiotherapy for children has not been considered from this broader, holistic perspective. In this theoretical paper, we will apply enactive concepts of embodiment, sensory-motor agency, coordination, and emergence to explore the concept and importance of touch in physiotherapists` clinical face-to face encounters with children. We will frame the discussion within the context of the typical sensorimotor development of children from the fetal stage to birth on and into adulthood. Moreover, we will rely on biological, physiological, and phenomenological insights to provide an extended understanding of the importance of touch and the significance of touch in clinical practice.